FABP7 controls radial glial scaffold stability during human cortical development - Yuanhao Wang; Xu Zhang; Ru Ba; Yimin Zhu; Hanwen Yu; Da Wang; Chu Chu; Xinyue Zhang; Yuan Hong; Shanshan Wu; Wanying Zhu; Min Xu; et al. (Proceedings of the National Academy of Sciences, 2026)
Radial glial (RG) cells serve as both neural progenitors and structural scaffolds for neuronal migration during cortical development. Although FABP7 has long been recognized as a marker of RG cells, its regulatory function has remained poorly defined. Using human fetal brain slices, embryonic mouse model, cerebral organoids, and assembloids, we demonstrate that FABP7 is essential for maintaining RG scaffold architecture and coordinating neuronal positioning. Single-cell analysis revealed that FABP7 deficiency induces transcriptional dysregulation, particularly affecting cytoskeletal organization, neural fate specification, and stress responses. Furthermore, transcriptomic features in FABP7 knockdown organoids exhibit convergence with neurodevelopmental disorders such as autism, alongside recapitulation of scaffold defects observed in idiopathic autism organoids. Mechanistically, FABP7 loss suppresses the mevalonate (MVA) pathway, resulting in impaired GTPase-mediated cytoskeletal organization and disruption of radial scaffold integrity. These findings identify FABP7 as a key regulator of cortical development and disease-relevant molecular programs, linking metabolic signaling to neurodevelopmental vulnerability.